Preparation of 1,2- and 1,4-dihydro derivatives of 6,7-dimethyl-2,3-diphenylquinoxaline via its dianion formed by reductive metallation - Kaban, Seniz; Aydogan, Feray (SPRINGER WIEN, 2008)
Treatment of 6,7-dimethyl-2,3-diphenylquinoxaline with sodium in tetrahydrofuran formed a monomeric dianion. The chemical behavior of this dianion was investigated by a variety of reagents. As the result, alkylation reactions gave 1,2-dihydro derivatives, while acylation reactions occured at 1,4-positions. Annulation of the pyrazine ring system was accomplished by treating the dianion with oligomethylene dichlorides, Cl(CH(2))(n)Cl, n = 2-4.
Keywords: heterocycles; reductions; nucleophilic substitutions; annulation; nitrogen anions; UNSATURATED HETEROCYCLIC-COMPOUNDS; ALKALI-METALS; RING-CLOSURE; RULES; Chemistry